Perilaku Hidup Bersih Dan Sehat Dalam Upaya Pencegahan Diare Pada SD Negeri Kota Makassar - Hilal, Achmad; Pannyiwi, Rahmat; Nurhaedah, Nurhaedah; Veradilla, Veradilla; Arnianti, Arnianti; Badaruddin, Badaruddin (Barongko: Jurnal Ilmu Kesehatan, 2025)
Clean and Healthy Living Behavior in schools is an activity to empower students, teachers and the school community to want to adopt a healthy lifestyle to create a healthy school. The purpose of this study was to determine the relationship between clean and healthy living behavior and diarrhea in elementary school students. The research method used was analytical study research with stratified random sampling, The results of the study stated that there was no diarrhea and good clean and healthy living behavior were 16 respondents (29.1%), while respondents who stated diarrhea and poor clean and healthy living behavior were 39 (70.9%). From the statistical results using the Chi Square statistical test with a degree of significance α = 0.05, a p value of 0.00 was obtained, this indicates that the p value <α, so it is concluded that the hypothesis (Hα) is accepted and the hypothesis (H0) is rejected. This means that there is a relationship between clean and healthy living behavior and diarrhea in elementary school students. The conclusion shows that there is a relationship between clean and healthy living behavior and diarrhea in elementary school students.